2020
DOI: 10.3332/ecancer.2020.1074
|View full text |Cite
|
Sign up to set email alerts
|

Training of oncologists: results of a global survey

Abstract: While several studies have highlighted the global shortages of oncologists and their workload, few have studied the characteristics of current oncology training. In this study, an online survey was distributed through a snowball method for cancer care providing physicians in 57 countries. Countries were classified into low-or lower-middle-income countries (LMICs), upper-middle-income countries (UMICs) and high-income countries (HICs) based on World Bank criteria. A total of 273 physicians who were trained in 5… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(8 citation statements)
references
References 19 publications
0
8
0
Order By: Relevance
“…Similar findings have been reported in studies in different regions of the world. 14 , 28 - 31 Findings from a study in Europe revealed that a majority of medical students rated clinical exposure to the management of patients with cancer as unsatisfactory. 28 Similarly, in Turkey, more than half of the nurses in one study did not receive any training regarding oncology palliative care.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…Similar findings have been reported in studies in different regions of the world. 14 , 28 - 31 Findings from a study in Europe revealed that a majority of medical students rated clinical exposure to the management of patients with cancer as unsatisfactory. 28 Similarly, in Turkey, more than half of the nurses in one study did not receive any training regarding oncology palliative care.…”
Section: Discussionmentioning
confidence: 99%
“…Ability versus inability to self-fund has implications for workforce selection and may increase disparities within and between countries, which may adversely affect the most disadvantaged populations and diminish the social accountability of training programs. 14 The majority of respondents in our study would like to have structured trainings on cancer research and statistical analysis. The demand for capacity building in cancer research that we identified aligns with findings in East Africa.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations